EFFECT OF STOCK MARKET VOLATILITY ON THE GROWTH OF CORPORATE BOND MARKET IN KENYA - Wanyama, Dr. David W. (International Journal of Finance, 2017)
Purpose: The purpose of this study was to analyze how stock market volatility influences the growth of corporate bond market in Kenya. Methodology: The study used descriptive and causal research designs. Secondary data was used. The sample of the study consisted of daily and monthly time series covering six years beginning January 2009 to December 2014. Unit root tests using Augmented Dickey-Fuller (ADF) and Phillips-Perron tests were done. The study used Eviews econometric software to facilitate empirical analysis of data. Results: Regression of coefficients results shows that stock market volatility and corporate bonds are positively and significant related (r=0.000023, p=0.0001). Unique Contribution to Theory, Practice and Policy: The study recommended that Policy makers should be aware of and monitor the level of stock market volatility that is appropriate for promoting the growth of the corporate bond markets and indeed other financial markets.